Utility Vectors To Fuzzy Preference Relations With Simple Additive Weighting (SAW) Method In New Employee Placement System - Eliasta Ketaren (International Journal of Information System and Innovative Technology, 2022)
To improve company performance, employees are one of the important elements in this regard, especially in the placement of new employees. The procedure for placing new employees in this case is carried out with Fuzzy Logic. The input parameters used are IQ Test, Psychological Test and Academic Test. To express the preferences of decision makers on the most desirable alternatives, it can be done by transforming the preference format of Utility Vectors to Fuzzy Preference Relation. Furthermore, choosing the SAW method to determine the weight value for each attribute, which is continued with the ranking process to select the best alternative, in this case it is a suitable alternative to determine the employee's work position in accordance with predetermined criteria. With this method, it is hoped that the assessment will be more precise and accurate because it is based on predetermined criteria and weights.